Feminicide: an approach with transforming vocation - Montoya Camarena, Ramsés Samael (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2019)
The text aims to demystify that biases are negative elements in decision making. Therefore, it is feasible that the biases form part of the probative reasoning through abduction. Specifically, they are analyzed two cases of feminicide of mexican and interamerican jurisdiction.